Sistem pembayaran e-zakat - Abdul Raub, Saadah (2008)
Online payment is one of an approach by electronic payment or better-known as e-payment. It capable to implement payment process through the network internet with simple way and fast without use the manual process. Parallel with progress of information technology (IT), institution of zakat as Majlis Agama Islam Negeri Johor (MAINJ) already diversify method of zakat payment to Muslim people in Johore state with a view to save time and simplify mode of zakat payment. These efforts are to make sure each group that qualified to pay zakat not give plenty of reason or to avoid from fulfil the rukun Islam. To achieve this project, System Development Life Cycle approach via waterfall model has been chosen as methodology. From observation, those carried out, present system obtain still do not efficient to promote zakat payer pay the zakat as one as compulsory. Overall from past research and up-to-date for issue and challenge of zakat, system developer find that efficiency in managing the collection of zakat, make the important element to give confidence to the payer zakat to pay off zakat through of institute that prescribed as MAINJ. More perfect system performance will increase revenue of zakat collection and simplify its distribution to asnaf asnaf that need. This affair is sure it can improve socio economic in Malaysia. To achieve the objective- purpose above then development of e-Zakat system is an alternative a most suitable in perform base to several characteristics of development which among others it use of state-of-the-art technology and sophisticated parallel with information technology development.